Zakat Management Improvement Strategy Efforts to Maintain Muzakki Trust - Muhammad Mujib Baidhowi; Ananto Triwibowo (Journal of Contemporary Applied Islamic Philanthropy, 2023)
Purpose: The management of zakat in Amil Zakat institutions is an important one, the management includes planning, organizing, implementing, and supervising activities as well as the distribution of funds. So that if an Amil Zakat institution has good management, it can increase the receipt of funds and public trust in the institution. In optimizing management, a mature strategy and plan are needed in order to produce maximum output. Methodology: In this study, the type of research used is Field Research, referred to as empirical research. While the nature of this study is quantitative, research provides an overview of particular community symptoms. In this study sampling using the Disproportionate Stratified Random Sampling method. Findings: The results of the research conducted show that the National Institute of Amil Zakat Baitul Maal Hidayatullah Yogyakarta has a good strategy in the management of zakat funds, while the strategy used includes careful planning, directed personal managerial, implementation of the collection and distribution of accordance with religious principles, as well as supervision conducted by a competent supervisor. This is what makes the National Amil Zakat institution Baitul Maal Hidayatullah always growing and increasing public confidence in the institution.